2000
DOI: 10.1007/bf03037787
|View full text |Cite
|
Sign up to set email alerts
|

Ökotoxikologische und humantoxikologische Risikobewertung PAK-belasteter Böden vor und nach biologischer Behandlung

Abstract: Ecotoxicological and Human Toxicological Risk Assessment of PAH-contaminated Soils Before and After Biological TreatmentThe goal of the present work is to assess the adverse effects of soil bound polycyclic aromatic hydrocarbons (PAH) which remain in soils after biological remediation. We focus on risk assessment for mammalian species with respect to the oral uptake of contaminated soil particles and compare the results of a biomarker test with those of an ecotoxicological assay, the bioluminescence inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We have shown here and in previous publications (Roos et al 1996(Roos et al , 2000 that ingestion of PAH-contaminated soil particles results in induction of CYP1A1 in the liver indicating successful mobilization and absorption of the contaminants in the gastrointestinal tract. The induction response in the liver correlates well with the amount of PAH with 5 and 6 aromatic rings present in the soils.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…We have shown here and in previous publications (Roos et al 1996(Roos et al , 2000 that ingestion of PAH-contaminated soil particles results in induction of CYP1A1 in the liver indicating successful mobilization and absorption of the contaminants in the gastrointestinal tract. The induction response in the liver correlates well with the amount of PAH with 5 and 6 aromatic rings present in the soils.…”
Section: Discussionmentioning
confidence: 62%
“…In previous papers, we have shown that hepatic CYP1A1 levels are increased upon ingestion of PAHcontaminated soil particles and that the levels correlate well with the amounts of 5-and 6-ring PAH in the soils (Roos et al 1994(Roos et al , 1996(Roos et al , 2000. Soil samples contaminated only with 3-and 4-ring PAH (1800 mg/kg soil) and devoid of higher condensates of PAH did not show significant effects on CYP1A1 expression in the liver after oral uptake.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations